Is acupoint injection the optimal way to administer mecobalamin for diabetic peripheral neuropathy? A meta-analysis and trial sequential analysis - Zhang, Fei; Yu, Yunfeng; Yin, Shuang; Hu, Gang; Yang, Xinyu; Tong, Keke; Yu, Rong (Frontiers in Neurology, 2023)
Objective Mecobalamin is a commonly used drug in the treatment of diabetic peripheral neuropathy (DPN). This study aimed to systematically evaluate the efficacy and safety of acupoint injection of mecobalamin for DPN. Methods Relevant clinical trials on acupoint injection of mecobalamin for DPN published before 31 January 2023 were searched in eight commonly used databases. After screening and confirming the included studies, meta-analysis and trial sequential analysis were performed. Results A total of 10 relevant studies were confirmed, and the total sample size was 927 cases. On the efficacy endpoints, meta-analysis showed that compared with other administration methods, acupoint injection of mecobalamin significantly increased the clinical effective rate by 27% [RR = 1.27, 95% CI = (1.19, 1.36), P < 0.00001], motor nerve conduction velocity (median nerve) by 5.93 m/s [MD = 5.93, 95% CI = (4.79, 7.07), P < 0.00001], motor nerve conduction velocity (common peroneal nerve) by 5.66 m/s [MD = 5.66, 95% CI = (2.89, 8.43), P < 0.0001], sensory nerve conduction velocity (median nerve) by 4.83 m/s [MD = 4.83, 95% CI = (3.75, 5.90), P < 0.00001], and sensory nerve conduction velocity (common peroneal nerve) by 3.60 m/s [MD = 3.60, 95% CI = (2.49, 4.71), P < 0.00001], and trial sequential analysis showed these benefits were conclusive. In terms of safety endpoints, meta-analysis indicated that the total adverse events for acupoint injection were comparable to other methods of administration, and trial sequential analysis suggested that the results needed to be validated by more studies. Subgroup analysis demonstrated that the benefits of acupoint injections of mecobalamin were not limited by the dose, duration of treatment, or number of acupoints reported in the included studies. Harbord's test showed no significant publication bias (P = 0.106). Conclusion The efficacy of acupoint injection of mecobalamin for DPN was significantly better than other administrations, and its safety was comparable to other administrations. Therefore, acupoint injection may be the optimal method of mecobalamin for DPN. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=454120, identifier: CRD42023454120.